Development and testing of a novel steel formwork for casting concrete slabs with different sizes (2017)
This paper describes and discusses the results of designing and implementing a steel formwork for casting and testing concrete slab specimens with different sizes. The formwork saves space, materials and costs due to the different configurations it may adopt, which allow, for instance, casting slabs with different sizes. The formwork avoids purchasing a greater number of formworks of particular dimensions, which increases costs and the space needed for storage. The formwork performance was assessed through the analysis of numerical results (strain and stress) obtained from simulations using finite element software. Performance was also verified during construction and testing of concrete slab specimens, reinforced with welded-wire meshes or steel fibers. The novel steel formwork herein presented and discussed is currently a patent pending in the Colombian Office of Industry and Commerce.